The T-type calcium channel CaV3.2 regulates bladder afferent responses to mechanical stimuli. Issue 5 (21st May 2023) - Grundy, Luke; Tay, Cindy; Christie, Stewart; Harrington, Andrea M.; Castro, Joel; Cardoso, Fernanda C.; Lewis, Richard J.; Zagorodnyuk, Vladimir; Brierley, Stuart M.
Abstract : Supplemental Digital Content is Available in the Text. Bladder sensory neurons express T-type calcium channel Cav 3.2, but not Cav 3.1 or Cav 3.3. Blocking Cav 3.2 inhibits bladder afferent sensitivity and bladder pain responses to distension. Abstract: The bladder wall is innervated by a complex network of afferent nerves that detect bladder stretch during filling. Sensory signals, generated in response to distension, are relayed to the spinal cord and brain to evoke physiological and painful sensations and regulate urine storage and voiding. Hyperexcitability of these sensory pathways is a key component in the development of chronic bladder hypersensitivity disorders including interstitial cystitis/bladder pain syndrome and overactive bladder syndrome. Despite this, the full array of ion channels that regulate bladder afferent responses to mechanical stimuli have yet to be determined. Here, we investigated the role of low-voltage-activated T-type calcium (CaV 3) channels in regulating bladder afferent responses to distension. Using single-cell reverse-transcription polymerase chain reaction and immunofluorescence, we revealed ubiquitous expression of CaV 3.2, but not CaV 3.1 or CaV 3.3, in individual bladder-innervating dorsal root ganglia neurons. Pharmacological inhibition of CaV 3.2 with TTA-A2 and ABT-639, selective blockers of T-type calcium channels, dose-dependently attenuated ex-vivo bladder afferent responses to distension in the absence of changes to muscle compliance. Further evaluation revealed that CaV 3.2 blockers significantly inhibited both low- and high-threshold afferents, decreasing peak responses to distension, and delayed activation thresholds, thereby attenuating bladder afferent responses to both physiological and noxious distension. Nocifensive visceromotor responses to noxious bladder distension in vivo were also significantly reduced by inhibition of CaV 3 with TTA-A2. Together, these data provide evidence of a major role for CaV 3.2 in regulating bladder afferent responses to bladder distension and nociceptive signalling to the spinal cord.